Bloodstone - Holzner, Nancy (A Deadtown novel, 2011)
The paranormal culprit known as the South End Reaper is straining the already-tense relations between Boston's human and inhuman residents. As the bodies pile up, Vicky Vaughn (Boston's only professional demon slayer), her formidable aunt, Mab, and her werewolf boyfriend, Kane, investigate-- only to find that the creature behind the carnage is after something much more than blood.